2010
DOI: 10.1002/chem.201000517
|View full text |Cite
|
Sign up to set email alerts
|

Triptycene‐Derived Calix[6]arenes: Synthesis, Structures, and Their Complexation with Fullerenes C60 and C70

Abstract: Two pairs of novel triptycene-derived calix[6]arenes 4a,b and 5a,b have been efficiently synthesized through both one-pot and two-step fragment-coupling strategies starting from 2,7-bis(hydroxymethyl)-1,8-dimethoxytriptycene 1. Subsequent demethylation of 4a,b and 5a,b with BBr(3) in dry dichloromethane gave the macrocyclic compounds 6a,b and 7a,b. Treatment of either 4a or 6a with AlCl(3) resulted in the same debutylated product 8, while 9 was similarly obtained from either 5a or 7a. Structural studies reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 57 publications
1
18
0
1
Order By: Relevance
“…This is similar to that of porphyrin/C 60 reported by Reed et al . In the fluorescence titration (Figures S12–S15), the fluorescence emissions of TBTTC at 509 nm are gradually quenched upon increasing the concentration of fullerenes. C 70 is more conspicuous than C 60 for fluorescence quenching.…”
supporting
confidence: 88%
“…This is similar to that of porphyrin/C 60 reported by Reed et al . In the fluorescence titration (Figures S12–S15), the fluorescence emissions of TBTTC at 509 nm are gradually quenched upon increasing the concentration of fullerenes. C 70 is more conspicuous than C 60 for fluorescence quenching.…”
supporting
confidence: 88%
“…We also obtained 4a (25%), 4b (20%), 5a (19%), and 5b (17%) by the fragment-coupling approach (Scheme 1, route b). 20 Treatment of 4a−b and 5a−b with BBr 3 produced the corresponding demethylated C2A2Ts 7a−b and 8a−b (Figure 2) in 71−78% yield. Treatment of 7a and 8a with AlCl 3 produced de-tert-butylated C2A2Ts 7c and 8c in 61 and 54% yield, respectively.…”
Section: Triptycene-derived Calixarenes Oxacalixarenes and Analogues ...mentioning
confidence: 99%
“…We also found that treatment of 4a and 5a with AlCl 3 in toluene directly gave 7c and 8c, respectively, in moderate yields. 20 Reaction of 2 with an excess of 2-methyl-1,3-dimethoxybenzene (9a) in CH 2 Cl 2 with BF 3 •Et 2 O as the catalyst gave 10a in 76% yield, which was then reacted with 2 in the presence of BF 3 •Et 2 O to afford 11a and 12a in 29 and 23% yield, respectively (Scheme 2). Demethylation of 11a and 12a by BBr 3 in CH 2 Cl 2 gave 13 and 14 in 86 and 83% yield, respectively.…”
Section: Triptycene-derived Calixarenes Oxacalixarenes and Analogues ...mentioning
confidence: 99%
“…Sar-tori等 [50] . 片段缩合方法也被陈传峰等 [52,53] 在2009年成功应 用于制备含有三联苯结构的杯 [6]芳烃衍生物. Wulff 等 [54,55] 也报道过一种基于双炔24与双(卡宾)配合物23 反应的方法(图14) [56] .…”
Section: 得到单取代的衍生物unclassified